Romania Toward a Low Carbon and Climate Resilient Economy : Marginal Abatement Cost Curve Analysis - World Bank (World Bank, Washington, DC, 2016)
The Marginal Abatement Cost Curves (MACC) analysis in the Romania Green Growth study presents a cross-sectoral outlook of the benefits and costs of the green technologies and abatement measures recommended in the sectoral modeling and analysis for the time period 2015-2050. MACC are a commonly used tool in evaluating emissions reduction technologies and a most efficient communication instrument for discussions of the abatement policies. Romania’s MACC is a combination of sectoral curves, each of which was built using the most appropriate approach for each sector. Global and local data sources were use in the MACC analysis. The findings are as follows: (i) sector analysis conducted for the Romania Green Growth Assessment resulted in a selection of a list of measures that constitute a green package in each sector of energy efficiency, powersupply, forestry, agriculture,and transport; (ii) a review by sector shows that energy efficiency measures are most beneficial, they have high abatement potential and mostly negative cost, while electricity supply interventions produce most of the abatement; (iii) agriculture and forestry measures are cost efficient and (iv) in transport, attacking emissions and generating local co-benefits justifies the high cost of the interventions and motivates support for improved transport policies. The conclusions and recommendations are as follows: (a) The MACC work derives from the analysis and modeling of all the relevant sectors in the Assessment; (b) when the MACC data from all sectors is modeled in one chart, it creates a clear and simple picture that compares green measures by costs and benefits across sectors; and (c) the Romania MACC can increase the quality of decisions regarding prioritizing and scheduling the proposed abatement measures.